Persuasive business presentations : using the problem-solution method to influence decision makers to take action - May, Gary L. (2013 digital library., 2014)
Business life is about persuasion. Effective managers advance their careers by identifying problems, developing solutions, and persuading decision makers to provide the support and resources necessary to make things happen. This book focuses on a specific presentation context: a problem-solution persuasive presentation to decision makers delivered in a conference room environment. Such presentations occur at every level in an organization. Therefore, team leaders, supervisors, managers, and executives can all benefit from learning how to design and deliver powerful presentations that move decision makers to take action. The author blends his extensive business experience with current research on persuasion to provide a practical, applied approach to using the problem- solution pattern. An integrated case study provides examples for each step in the process. The result is a useful, actionable guide that will help professionals from every field make a difference in their organization.